Experimental investigation of phase equilibria in the Ti-Fe-Zr system. (June 2018) - Zeng, Lijun; Xu, Guanglong; Liu, Libin; Bai, Weimin; Zhang, Ligang
Abstract: The phase relations of the Ti-Fe-Zr system at 873 and 1173 K were experimentally investigated by using the equilibrated alloys. Four ternary phases were determined stable at 1173 K. Two of them were line compounds with fixed Fe/(Ti, Zr) ratio, while the other two showed ellipse-shaped homogeneity. There were eight three-phase equilibria and a continuous single phase field of β(Ti, Zr) in the isothermal section at 1173 K. The solubility of Zr in Fe2 (Ti, Zr) and Ti in (Fe, Ti)2 Zr was measured to be 25.5 at% and 6.1 at%, respectively. The remaining binary intermetallic phases hardly dissolved the third component. The phase relationships in the isothermal section at 873 K were similar to those at 1173 K over the composition range of 0–50 at% Fe. In this isothermal section, five three-phase equilibria were observed and they were all related with the newly found ternary phases. The phase relations measured in this work are of significant difference from the existing ones obtained with the diffusion couple. Highlights: Phase equilibria of the Ti-Fe-Zr system were investigated by using equilibrate alloys. Four stable ternary compounds were newly found in this system. Phase relations obtained in this work differ significantly from those determined with the diffusion couple.